Shapeshifting the Scottish Borders: A Geopoetic Dance of Place - Claire Pençak (Arts, 2019)
In this paper, I unite dance theory and practice and geopoetics in order to reflect on edges, peripheries and borders in a geographic region, the Scottish Borders, where the dominant cultural narrative is and has historically been based on rivalry. I draw here on the writing of the Scottish poet-philosopher Kenneth White, the practices of specific dancers and choreographers and on relational accounts of place and more-than-human perspectives. Rather than ‘sense of place’, my interest is in sensing place and thinking through sites. Threaded throughout are descriptions of perception practices exploring woodland, stone and riverways, which take the reader into the more experiential realm of embodied knowing. These passages are an invitation to be present with more-than-human others, to be in contact with the vitality of materials and to allow for being shaped, rather than being the shaping force. The intention is to bring different bodies of knowledge into contact as a way of revealing other vocabularies within place, which suggest alternative cultural narratives and help create the conditions for place—making a more collaborative, ethical and less anthropocentric endeavour, open to the influence and organising principles of the more-than-human.